High Leptin Level Attenuates Embryo Development in Overweight/Obese Infertile Women by Inhibiting Proliferation and Promotes Apoptosis in Granule Cell - Lin, Xian-hua; Wang, Hui; Wu, Dan-dan; Ullah, Kamran; Yu, Tian-tian; Ur Rahman, Tanzil; Huang, He-feng (Hormone and Metabolic Research, 2017)
Obesity appears to be associated with female reproductive dysfunction and infertility. Women with obesity undergoing in vitro fertilization (IVF) had poor oocyte quality, decreased embryo development, and poor pregnancy outcome. However, the mechanism linking obesity to poor reproductive outcomes is still unclear. Obesity is frequently accompanied with elevated leptin levels. Here we aimed to evaluate the effect of high leptin level in follicular fluid (FF) on the proliferation and apoptosis in granule cells and correlate these findings with poor reproductive outcomes in infertile women with overweight or obesity who underwent IVF treatment. We investigated clinical and ongoing pregnancy rates in 189 infertile women who underwent IVF. Leptin levels were quantified in peripheral blood and FF as well. In vitro cell model was used to explore the potential effect of high leptin on the proliferation and apoptosis in granulosa cells. Results showed reduced clinical and ongoing pregnancy rates in overweight/obesity women who underwent IVF compared to control with normal BMI. On the other hand, leptin levels presented significant increase in peripheral blood and FF in overweight/obese women. Leptin level in FF was negatively correlated to good quality embryo rate. Importantly, in vitro study showed that leptin inhibited cells proliferation and promoted apoptosis by upregulation of caspase-3 and downregulation of Bcl-2 in granulosa cells in a dose dependent manner. These observations suggest that leptin may acts as a local mediator to attenuate embryo development and reduce fertility in obese patients.
Keywords: obesity; leptin; good quality embryo; pregnancy rate; granule cells